The SORA package for Stellar Occultations: sub-mas precision technique - Gomes-Júnior, A. R. (2025)
Stellar occultation is an event that happens when a solar system object passes in front of a background star. It is a unique and powerful technique to probe rings [13], satellites [4], topography [5], atmospheres [6], and other physical characteristics of the occulting body. The technique translates temporal resolution into spatial resolution, achieving sub-milliarcsecond (submas) accuracy in the relative position of the object and star when supported by high signal-to-noise observations. However, the absolute position remains limited by the star's cataloged coordinates.